LOSS AND RECOVERY OF EXCITABILITY BY NORMAL AND BY DEGENERATING NERVES DEPRIVED OF SODIUM - Gallego, A. (The Rockefeller University Press, 1951)
A study has been made of the loss of excitability in a sodium-free medium and of the recovery of excitability in Ringer's solution by A fibers of normal frog nerves and of nerves in advanced stages of Wallerian degeneration. With normal nerves that are being kept in a sodium-free medium the number of conducting fibers does not undergo a readily detectable decrease in less than 1 to 2 hours; inexcitability of all the A fibers does not develop in less than 7 to 8 hours. During the development of inexcitability the speed of conduction of the still conducting fibers undergoes a progressive decrease; in advanced stages the speed of conduction is not more than one-fifth of the normal speed. The nerve fibers lose the ability to conduct rhythmic trains of impulses earlier than the ability to conduct single impulses. The recovery of excitability in Ringer's solution duplicates in a reverse order the sequence of changes that have been previously observed during the development of inexcitability. The rate of the recovery of excitability in Ringer's solution is higher than the rate of the loss of excitability in the sodium-free medium. With degenerating nerves the effect of the lack of sodium develops qualitatively in the same manner in which it develops with normal nerves. Degenerating nerve fibers, however, become inexcitable in a sodium-free medium earlier than normal fibers. The recovery of the excitability in Ringer's solution takes place in much the same manner in normal and in degenerating nerve fibers. The loss of excitability during Wallerian degeneration is a process that develops simultaneously, or practically so, throughout the entire length of the fibers. The nerve fibers retain a great deal of functional ability throughout the several days which precede the onset of inexcitability and then suddenly become inexcitable.